Synthesis of ultrafine LiCoO2 powders by the sol-gel method - Sun, YK; Oh, IH; Hong, SA (CHAPMAN HALL LTD, 1996)
Ultrafine high-temperature (HT) LiCoO2 powders were synthesized by the sol-gel method using polyacrylic acid (PAA) as a chelating agent. The decomposition process of the gel precursor was examined to determine the crystallization temperature and the dependence of the physicochemical properties of HT-LiCoO2 powders on the PAA quantity was extensively investigated. Polycrystalline HT-LiCoO2 powders, composed of very uniformly sized ultrafine particulates with an average particle size of 30-50 nm and a specific surface area of 2.3-17 m(2)g(-1), could be obtained at the lower calcination temperature of 550 degrees C and the shorter calcination time of 1 h compared to the solid-state reaction.
Keywords: POLY(ACRYLIC ACID); CITRATE PROCESS; PHASE; ELECTROCHEMISTRY; CARBONATE; LIXCOO2